2023
DOI: 10.1111/jnc.15773
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment reveals a novel role for lysosomes in oligodendrocyte maturation

Abstract: White matter deficits are a common neuropathologic finding in neurologic disorders, including HIV‐associated neurocognitive disorders (HAND). In HAND, the persistence of white matter alterations despite suppressive antiretroviral (ARV) therapy suggests that ARVs may be directly contributing to these impairments. Here, we report that a frontline ARV, bictegravir (BIC), significantly attenuates remyelination following cuprizone‐mediated demyelination, a model that recapitulates acute demyelination, but has no im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Moreover, induction of the autophagy/ lysosomal process is known to promote oligodendrocyte maturation [62] and lysosomes are increasingly recognized as central drivers in lipid trafficking and catabolism for the production and recycling of myelin [63,64]. On the other hand, lysosomal alkalinization was recently demonstrated to be sufficient to induce a delay in oligodendrocyte maturation [65], supporting a direct impact of the lysosomal impairment generated by β-glucocerebrosidase dysfunction in this context. Interestingly, disrupted cholesterol trafficking, leading to a punctate distribution as displayed by Oli-neu cells upon β-glucocerebrosidase inactivation, was also found to reduce oligodendrocyte differentiation in an Alzheimer's disease in vitro context, a defect that can be recovered by cyclodextrin that facilitates cholesterol transport to the membrane [66].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, induction of the autophagy/ lysosomal process is known to promote oligodendrocyte maturation [62] and lysosomes are increasingly recognized as central drivers in lipid trafficking and catabolism for the production and recycling of myelin [63,64]. On the other hand, lysosomal alkalinization was recently demonstrated to be sufficient to induce a delay in oligodendrocyte maturation [65], supporting a direct impact of the lysosomal impairment generated by β-glucocerebrosidase dysfunction in this context. Interestingly, disrupted cholesterol trafficking, leading to a punctate distribution as displayed by Oli-neu cells upon β-glucocerebrosidase inactivation, was also found to reduce oligodendrocyte differentiation in an Alzheimer's disease in vitro context, a defect that can be recovered by cyclodextrin that facilitates cholesterol transport to the membrane [66].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mRNA expression of the mature marker proteolipid protein (PLP) was also decreased, suggesting that EVG interfered with the maturation process at the transcriptional level. Alteration of oligodendrocyte differentiation has been reported for several antiretroviral drugs in the protease inhibitor class ( Jensen et al, 2015 ; Festa et al, 2021 ) and the integrase strand transfer inhibitor (INSTI) class ( Roth et al, 2020 ; Festa et al, 2023 ). We previously demonstrated that the INSTI raltegravir (RAL) did not inhibit oligodendrocyte differentiation ( Roth et al, 2020 ), and here, we show that the expression of SREBP-1 and SREBP-2 in oligodendrocytes was not affected by RAL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent white matter damage is often observed in persons with HIV on antiretroviral therapy. Although HIV infection itself can cause white matter injury, antiretroviral toxicity may contribute to or prolong myelin damage by altering oligodendrocyte maturation and myelin formation and/or maintenance (Jensen et al, 2015;Roth et al, 2020;Festa et al, 2021Festa et al, , 2023. This, in turn, may help explain at least in part, the high prevalence of HAND among persons with HIV EVG triggers the integrated stress response (ISR) in oligodendrocyte cultures, but the integrated stress response inhibitor (ISRIB) minimally prevents EVG-induced SREBP alterations.…”
Section: Discussionmentioning
confidence: 99%